Breakthrough cases of mpox: One-dose vaccination is associated with milder clinical manifestations - Robert Allard; Pascale Leclerc; Geneviève Bergeron; Geneviève Cadieux (Elsevier, 2024)
Background: Very few studies have investigated the effectiveness of vaccination in decreasing the severity of breakthrough mpox. Our goal was to estimate the strength of the associations between recent mpox vaccination with MVA-BN and various clinical manifestations of the disease. Methods: Telephone interviews using standardized questionnaires, upon notification and 28 days later, of the 403 persons with mpox reported to Montreal Public Health in 2022. MVA-BN vaccination data were obtained from the provincial immunization registry. The main outcomes were numbers of skin lesions and body sites affected, other clinical manifestations (OCM) compatible with mpox, complications, and hospitalization. Findings: 155 persons with mpox (39% of 403) had received 1 dose of vaccine at least 14 days before symptom onset. One-dose vaccination, adjusting for age and HIV status, was significantly associated with fewer lesions, sites affected with lesions, and OCMs. HIV-positive persons with breakthrough mpox reported significantly more lesions, sites affected, and OCMs at initial interview, than HIV-negative ones. However, vaccination was associated with a lower risk of all outcomes to the same degree irrespective of HIV status. Interpretation: One dose of MVA-BN vaccine was about 60% effective in decreasing the frequency and extent of clinical manifestations, among both HIV-positive and HIV-negative persons with breakthrough mpox. Beyond preventing infection, mpox vaccination can be promoted to reduce clinical manifestations in persons at risk for mpox, even if HIV+ . Funding: This work used data obtained as part of Montreal Public Health's 2022 mpox outbreak response and received no external funding.